Analysis Of The Influence Of Company Performance, Institutional Ownership, Company Size And Debt Policy On Company Value Of Property And Construction Companies In Indonesia - Umi Zunaidah; Walla Astianty Putri; Donny Dharmawan; Loso Judijanto; Ngurah Pandji Mertha Agung Durya (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
The purpose of this study is to determine if the factors that affect company value in the property, real estate, and building construction sectors are institutional ownership, debt policy, company size, and company performance. The companies that are listed on the Indonesia Stock Exchange (BEI) in the categories of real estate, property, and building construction comprise the study's population. Purposive sampling was the method of sampling that was employed in this study. Quantitative data, also known as secondary data, was used in this study. Documentation and a review of the literature were utilized to gather the data for this study. A panel data regression test is the research methodology employed in this study. The regression test results demonstrate that the independent variables of institutional ownership, debt policy, performance, and size have a noteworthy positive impact on the value of the company. Property, real estate, and building construction companies have demonstrated a noteworthy positive impact on their company value due to the institutional ownership variable. In the real estate, building construction, and property industries, it has been demonstrated that the debt policy variable significantly increases the value of the company. In the real estate, building construction, and property industries, it has been demonstrated that company performance variables significantly increase the value of the company. In the real estate, building construction, and property industries, it has been demonstrated that the company size variable has no bearing on the value of the company.